Negative Impacts of Online Gambling Reviewed from The Social Economic and Psychological Perspective in Accordance with Undergoing No. 1 of 2024 on Second Amendment to Undergoing Number 11 of 2008 on Information and Transactions - Dellia Putri Octavia; Taufiq Nugroho (Universitas Muhammadiyah Surakarta, 2024)
This study presents an in-depth review of the negative impacts of online gambling practices, particularly in the social, economic, and psychological contexts, in accordance with the latest regulations set out in Law No. 1 of 2024. This study uses a qualitative approach with a literature review method to analyze the negative impact of online gambling from a socio-economic and psychological perspective, as well as evaluating its compatibility with Law No. 1 of 2024 on the Second Amendment to Law No. 11 of 2008 on Electronic Information and Transactions. This article presents a new understanding of the impact of online gambling by comprehensively considering social, economic, and psychological aspects, as well as highlighting relevant recent regulatory changes. The results show that the practice of online gambling has a significant negative impact on various aspects of people’s lives, including financial problems, social conflicts, and mental health issues. In the context of Law No. 1 Year 2024, this study confirms the need for more decisive action in addressing the negative impacts of online gambling, both through stricter regulations and more effective rehabilitation programs.